Future Ratboy and the quest for the missing thingy - Smith, James (Egmont UK Ltd. London, 2017)
When a bolt of lightning hit Colin Lamppost he was zapped millions of years into the future and turned into a half boy, half rat, half TV! With new superkeel powers and a real life sidekick in Not Bird, Future Ratboy was born. In this new adventure, Future Ratboy sees a surprising new side to his enemy, evil Mr. X, goes on a journey to the Planet Bin and faces a race against time to find the missing thingy